Progress in the Utilization Efficiency Improvement of Hot Carriers in Plasmon-Mediated Heterostructure Photocatalysis - Tong Zhang (Applied Sciences, 2019)
The effect of plasmon-induced hot carriers (HCs) enables the possibility of applying semiconductors with wide band gaps to visible light catalysis, which becomes an emerging research field in environmental protections. Continued efforts have been made for an efficient heterostructure photocatalytic process with controllable behaviors of HCs. Recently, it has been discovered that the improvement of the utilization of HCs by band engineering is a promising strategy for an enhanced catalytic process, and relevant works have emerged for such a purpose. In this review, we give an overview of the recent progress relating to optimized methods for designing efficient photocatalysts by considering the intrinsic essence of HCs. First, the basic mechanism of the heterostructure photocatalytic process is discussed, including the formation of the Schokkty barrier and the process of photocatalysis. Then, the latest studies for improving the utilization efficiency of HCs in two aspects, the generation and extraction of HCs, are introduced. Based on this, the applications of such heterostructure photocatalysts, such as water/air treatments and organic transformations, are briefly illustrated. Finally, we conclude by discussing the remaining bottlenecks and future directions in this field.